MENINGKATKAN KEPUASAN KERJA KARYAWAN MELALUI PERENCANAAN KARIR INDIVIDU - Rahmi Widyanti; Basuki Basuki; Mursanto Mursanto (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2021)
The future is something that is uncertain for humans. Therefore, everyone tries to predict and plan for his/her future. Individual career planning is an important way to secure life. A career plan will help employees feel comfortable with their work and will directly affect job satisfaction. This study aims to analyze the relationship between individual career planning and employee job satisfaction for two types of university workers  –  academic  and  administrative  staff.  This  research  is  also  to  understand whether the influence of individual career planning on job satisfaction is positive and significant. The research instrument using a questionnaire was distributed to 100 respondents  at  Uniska  Banjarmasin.  Statistical  analysis  with  linear  regression  and tested using SPSS software for windows version 20.0.The results of the study found that the existence of a clear career planning from the organization can increase job satisfaction positively and significantly.